Sacrificial-layer free transfer of mammalian cells using near infrared femtosecond laser pulses. - Jun Zhang; Bastian Hartmann; Julian Siegel; Gabriele Marchi; Hauke Clausen-Schaumann; Stefanie Sudhop; Heinz P Huber (PLoS ONE, 2018)
Laser-induced cell transfer has been developed in recent years for the flexible and gentle printing of cells. Because of the high transfer rates and the superior cell survival rates, this technique has great potential for tissue engineering applications. However, the fact that material from an inorganic sacrificial layer, which is required for laser energy absorption, is usually transferred to the printed target structure, constitutes a major drawback of laser based cell printing. Therefore alternative approaches using deep UV laser sources and protein based acceptor films for energy absorption, have been introduced. Nevertheless, deep UV radiation can introduce DNA double strand breaks, thereby imposing the risk of carcinogenesis. Here we present a method for the laser-induced transfer of hydrogels and mammalian cells, which neither requires any sacrificial material for energy absorption, nor the use of UV lasers. Instead, we focus a near infrared femtosecond (fs) laser pulse (λ = 1030 nm, 450 fs) directly underneath a thin cell layer, suspended on top of a hydrogel reservoir, to induce a rapidly expanding cavitation bubble in the gel, which generates a jet of material, transferring cells and hydrogel from the gel/cell reservoir to an acceptor stage. By controlling laser pulse energy, well-defined cell-laden droplets can be transferred with high spatial resolution. The transferred human (SCP1) and murine (B16F1) cells show high survival rates, and good cell viability. Time laps microscopy reveals unaffected cell behavior including normal cell proliferation.